Reasons for discontinuation of novel oral anticoagulant therapy in patients with atrial fibrillation. (2nd April 2020) - Mitrovic, Darko; Folkeringa, Richard; Veeger, Nic; van Roon, Eric
Abstract: Aims: We sought to investigate the reasons for, and rates of, novel oral anticoagulant (DOAC) therapy discontinuation. Methods: This was an observational cohort study of patients with atrial fibrillation (AF) referred to a regional DOAC outpatient clinic between February 2013 and October 2017. The study population consisted of 875 consecutive patients with AF who visited the DOAC outpatient unit to initiate treatment with apixaban ( N = 303), dabigatran ( N = 267) or rivaroxaban ( N = 305) for long-term ischemic stroke prophylaxis. All the patients came from the Leeuwarden Medical Center cardiology outpatient clinic, which offers a well structured and nurse-run DOAC unit in cooperation with the hospital's thrombosis service. This clinic operates according to the Dutch nationwide guidelines on integration of anticoagulation services. Results: Overall rate of discontinuation was 11.9 per 100 patient-years of follow-up. Discontinuation rates for apixaban, dabigatran and rivaroxaban were 8.1, 16.6 and 11.5 per 100 patient-years of follow-up. Apixaban had the lowest rate of discontinuation during the 36 month follow-up period. Dabigatran and rivaroxaban had high discontinuation rates during the 3–6 month period following DOAC therapy initiation. The main reasons for discontinuation of DOAC therapy were adverse side effects, patient-initiated discontinuation and any bleed. Limitation: This was a retrospective and non-randomized study, and our results should be interpreted in light of these observations. Conclusion: DOAC discontinuation rates varied significantly and appeared related to drug-specific side effects, patient-initiated discontinuation and bleeding. We observed longer-term administration of apixaban, suggesting that this drug is better tolerated than dabigatran or rivaroxaban.